Sleep quality of adult psychiatric outpatients at Chris Hani Baragwanath Academic Hospital - Celeste M. Harlies; Wendy Friedlander (South African Journal of Psychiatry, 2023)
Background: Sleep disorders are increasingly prevalent among the general population and individuals with mental disorders. However, little research has focused on the sleep quality of psychiatric patients beyond depression, despite its relevance in diagnostic criteria.